Pelatihan Membatik Bagi Masyarakat Semaki Gede, Semaki, Kecamatan Umbulharjo Kota Yogyakarta - Wiyata, Sri; Suwartini, Sri; Jihad Kuncoro, Muh. Aryos (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2022)
The Special Region of Yogyakarta requires every district in its territory to have a characteristic batik motif. However, the Umbulharjo District does not yet have the characteristics of a batik motif, so it is necessary to make a written batik motif design that symbolizes the beauty of the Umbulharjo District. It turns out that many people in the sub- district have below-average economic capacity. Therefore this community service is carried out by training in batik writing motifs for the community Umbulharjo sub-district, especially in the Semaki Gede, Semaki area. The PkM team and Ibu Ratu Hemas were entrusted with establishing a place to make batik houses. So that batik activities can be carried out in a comfortable place. This training is expected to produce batik artisans for the Umbulharjo District later.